2018
DOI: 10.1371/journal.pone.0198829
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal care could be the key to improving the continuum of care in maternal and child health in Ratanakiri, Cambodia

Abstract: In South-East Asia, the maternal and child mortality rate has declined over the past decades; however, it varies among and within the countries in the region, including Cambodia. The continuum of care is an integrated series of care that women and children are required to avail continuously from pregnancy to the child/motherhood period. This study aimed to assess the completion rate of the continuum of care and examine the factors associated with the continuum of care in Ratanakiri, Cambodia. A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
87
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 28 publications
16
87
6
1
Order By: Relevance
“…In this study the level of continuum of care was 9.7%[95% CI: 6.9%, 12.5%] which is consistent with findings from study in Tanzania (10%) [17] but higher than study conducted in Cambodia (5%) [23], and lower than studies conducted in Pakistan (27%) and Egypt (50.3%) [21,22]. The possible reason in this study might be due to time variation, variation in study design, and variation in source of data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study the level of continuum of care was 9.7%[95% CI: 6.9%, 12.5%] which is consistent with findings from study in Tanzania (10%) [17] but higher than study conducted in Cambodia (5%) [23], and lower than studies conducted in Pakistan (27%) and Egypt (50.3%) [21,22]. The possible reason in this study might be due to time variation, variation in study design, and variation in source of data.…”
Section: Discussionsupporting
confidence: 90%
“…Women were classified as not completed the continuum of care if they missed any one of the above visits/attendances at any level. [17,[21][22][23].…”
Section: Definition and Measurement Of Variables Of The Studymentioning
confidence: 99%
“…It is an essential element across the continuum of care in the maternal and child health care services, and serve as a gateway for family planning services. Woman and her partner/family require more information than they usually receive on the care of the baby and mother within the rst week after childbirth, to stay safe from maternal and neonatal complications [5].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the reason will be the need to the improved skilled worker and health awareness. This study found that postnatal care was significantly negative associated with improving the continuum of care maternal and child health in Ratanakiri, Cambodia [15]. Skilled delivery of essential maternal and perinatal care practices that to reduce maternal and new-born injury [16].…”
Section: Discussionmentioning
confidence: 82%